Association of Urinary N7-(1-hydroxyl-3-buten-1-yl) Guanine (EB-GII) Adducts and Butadiene-Mercapturic Acids with Lung Cancer Development in Cigarette Smokers - Jokipii Krueger, Caitlin C.; Park, Sungshim L.; Patel, Yesha; Stram, Daniel O.; Aldrich, Melinda; Cai, Qiuyin; Tretyakova, Natalia Y. (Chemical research in toxicology, 2024)
Approximately 10% of smokers will develop lung cancer. Sensitive predictive biomarkers are needed to identify susceptible individuals. 1,3-Butadiene (BD) is among the most abundant tobacco smoke carcinogens. BD is metabolically activated to 3,4-epoxy-1-butene (EB), which is detoxified via the glutathione conjugation/mercapturic acid pathway to form monohydroxybutenyl mercapturic acid (MHBMA) and dihydroxybutyl mercapturic acid (DHBMA). Alternatively, EB can react with guanine nucleobases of DNA to form N7-(1-hydroxyl-3-buten-1-yl) guanine (EB-GII) adducts. We employed isotope dilution LC/ESI-HRMS/MS methodologies to quantify MHBMA, DHBMA, and EB-GII in urine of smokers who developed lung cancer (N = 260) and matched smoking controls (N = 259) from the Southern Community Cohort (white and African American). The concentrations of all three biomarkers were significantly higher in smokers that subsequently developed lung cancer as compared to matched smoker controls after adjusting for age, sex, and race/ethnicity (p < 0.0001 for EB-GII, p < 0.0001 for MHBMA, and p = 0.0007 for DHBMA). The odds ratio (OR) for lung cancer development was 1.63 for MHBMA, 1.37 for DHBMA, and 1.97 for EB-GII, with a higher OR in African American subjects than in whites. The association of urinary EB-GII, MHBMA, and DHBMA with lung cancer status did not remain upon adjustment for total nicotine equivalents. These findings reveal that urinary MHBMA, DHBMA, and EB-GII are directly correlated with the BD dose delivered via smoking and are associated with lung cancer risk.